The Relationship Between Learning Styles and Learning Motivation Towards Academic Achievement of Students of The Faculty Of Economics and Business, State University of Makassar - Abdul Rahman (Economics and Business Journal (ECBIS), 2025)
This study aims to determine the effect of learning styles on academic achievement, the effect of learning motivation on academic achievement, and the effect of learning styles and learning motivation on academic achievement. Sampling was carried out using a simple purposive sampling technique so that 44 students were obtained. Data collection used an online questionnaire. Data analysis used multiple linear regression analysis. The results of the study showed that the partial test (t-test) concluded that learning styles had a significant effect on academic achievement and learning motivation had a significant effect on academic achievement. Based on the F test, it was concluded that learning styles and learning motivation jointly influenced the learning achievement of FEB students at Makassar State University. Therefore, teachers are advised to analyze student learning styles in determining teaching methods and always motivate students to increase the intensity of their learning efforts.